'All You Can Do is Pray': Implications for Human Rights Advocacy of the Lack of Recognition of Ethnic Cleansing as an International Crime on its Own. (26th December 2018) - Qerimi, Qerim
Abstract: This policy note examines the implications for advocacy which follow from the rather obscure and confusing relationship between one of the most odious human experiences, ethnic cleansing, and the system of international law. From the very distant history of Assyria to, among others, the most contemporary disturbing displacements of human beings from Darfur (Sudan), Aleppo (Syria), and of the Rohingya from Myanmar, the policy widely known as ethnic cleansing has resisted time to maintain its indeterminate legal existence. Neither the more recent 2015 ( Croatia v. Serbia ) nor the 2007 ( Bosnia and Herzegovina v. Serbia and Montenegro ) genocide cases have cured the plague. To the contrary, the International Court of Justice (ICJ) has remained faithful to its statement that ethnic cleansing has no legal significance of its own. This policy note draws attention to the impact that an ill-defined 'policy' or practice exerts on human rights advocacy, weakening its effectiveness and diminishing its results.